Rotación de personal y eficiencia en el gasto público municipal - Bustamante, Ivan; Arias, Glemar; Cotrado, Sheylla; Quispe, Estela (2023)
The book is adapted from an investigation presented to the Universidad Nacional San Antonio Abad del Cusco, whose objective was to determine if staff turnover is a factor of efficiency and public spending in the District Municipality of Echarati, Cusco (Peru). For this purpose, a quantitative approach was followed; with scope is descriptive - analytical, non-experimental design. The sample that was used is census considering all the personnel considered in the transparency reports: 115 for the December 2018 period and 90 for the January 2019 period. The technique applied for the investigation was the collection of data through the MEF and as instrument, the data collection form was used. It was determined that there is a degree of influence of staff turnover on the efficiency and public spending of the analyzed municipality, so it can be considered an efficiency factor. On the other hand, the turnover of personnel of the District Municipality of Echarati during the period 2018 - 2019, is high, causing public spending of 23.38 ± 8.8% in the first semester of 2018 and an average of 15, 07 ± 10.89% for the year 2019.
Keywords: staff turnover; public spending; public management; municipal management